2010
DOI: 10.1136/bjsm.2009.066456
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and non-allergic rhinitis in swimmers: clinical and cytological aspects

Abstract: A neutrophilic rhinitis occurs in a large proportion of swimmers. This seems to be irritative in its nature and can be prevented by avoiding the direct contact with chlorinated water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 19 publications
2
54
0
Order By: Relevance
“…19 In our study, all subjects with a positive skin prick test had eosinophils in their nasal smear; thus, allergic rhinitis was more prevalent in indoor pool workers than neutrophilic rhinitis, even though neutrophilic rhinitis has been previously reported in swimmers. 8 In the skin prick test, 29.6 per cent of subjects in the study group and 18.4 per cent in the control group tested positive. Indoor pool workers had a high prevalence of allergies (as determined by comparing the skin prick test and eosinophil count results with the control group).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…19 In our study, all subjects with a positive skin prick test had eosinophils in their nasal smear; thus, allergic rhinitis was more prevalent in indoor pool workers than neutrophilic rhinitis, even though neutrophilic rhinitis has been previously reported in swimmers. 8 In the skin prick test, 29.6 per cent of subjects in the study group and 18.4 per cent in the control group tested positive. Indoor pool workers had a high prevalence of allergies (as determined by comparing the skin prick test and eosinophil count results with the control group).…”
Section: Discussionmentioning
confidence: 98%
“…Gelardi et al reported predominantly neutrophilic inflammation and allergic rhinitis in symptomatic swimmers and suggested that this could be prevented by avoiding direct contact with chlorinated pool water. 8 Unlike other reports, in our study, we evaluated the nasal cytology of indoor pool workers who had no direct contact with the swimming pool to assess the indirect effect of the evaporation of airborne chlorine. In contrast to Gelardi et al 8 we did not find significant numbers of neutrophils in the nasal smears, and considered that this was likely due to the lack of contact between the nasal mucosa and the pool water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations